Vitamin D Deficiency Is Highly Prevalent in Critically Ill Patients and a Risk Factor for Mortality: A Prospective Observational Study Comparing Noncirrhotic Patients and Patients With Cirrhosis. (October 2020) - Mayr, Ulrich; Fahrenkrog-Petersen, Leonie; Batres-Baires, Gonzalo; Rasch, Sebastian; Herner, Alexander; Schmid, Roland M.; Huber, Wolfgang; Lahmer, Tobias
Introduction: A 25-hydroxyvitamin D, 25(OH)D, deficiency is common among critically ill patients and correlated with increased mortality. Furthermore, deficiency is associated with advanced liver disease. However, there are no studies available comparing the dimensions and consequences of a 25(OH)D deficiency between patients with and without liver cirrhosis in the setting of intensive care units (ICUs). This study focuses on differences in 25(OH)D status between critically ill noncirrhosis patients and patients with cirrhosis (primary end point), hypothesizing that deficiency and its impact on mortality risk are even more pronounced in patients with cirrhosis. Methods: We performed a prospective observational study of 176 patients (noncirrhosis patients, N = 114; patients with cirrhosis, N = 62) with a laboratory assessment of 25(OH)D on ICU admission and survival analyses after 180 days. Results: On admission, 55% of patients showed a severe deficiency, 25(OH)D <10 ng/mL, and a further 23% moderate deficiency (10-19 ng/mL). The overall median level of 25(OH)D was 8.0 (5.0-18.0) ng/mL (10.5 [6.0-21.3] in noncirrhosis patients vs 7.0 [4.8-10.0] in patients with cirrhosis; P < .001). We found extremely low levels particularly in patients without prior vitamin D supplementation (6.0 [4.0-7.5] in patients with cirrhosis vs 8.0 [5.0-12.0] ng/mL in noncirrhosis patients; P = .004). Vitamin D status correlated inversely with the sequential organ failure assessment, acute and physiology chronic health evaluation, model of end-stage liver disease, and Child-Pugh scores. Survival analyses categorized 25(OH)D levels <10 ng/mL as a high-risk factor for mortality 180 days after admission (hazard ratio [HR]: 2.45, 95% confidence interval [CI] = 1.60-3.70; P < .001). In patients with cirrhosis, a severe deficiency (<10 ng/mL) involved a significantly higher mortality risk than in noncirrhosis patients (HR: 2.30, 95% CI = 1.39-3.82; P = .001). In cases of admission levels ≥10 ng/mL, however, mortality risk was similar between patients with cirrhosis and noncirrhosis patients (HR: 1.08, 95% CI = 0.43-2.73; P = .873). Conclusions: Hypovitaminosis D is a highly frequent disorder in critically ill patients admitted to ICU. A severe deficiency with levels <10 ng/mL is a high risk factor for increased mortality, especially in patients with cirrhosis.